Teknologi, Budaya SUMANG OPAT Tanah Gayo dan Kepanikan Moral - Addahri Hafidz Awlawi (Jurnal Psikologi Islam dan Budaya, 2021)
This study aims to explore the issue of Sumang and moral panic including the level of understanding of adolescents, and forms and causes of violation of Sumang's values. The research method used qualitative with a case study approach. The research subjects consisted of 35 adolescents (14-20 years), 2 Guidance Counseling teachers, 3 parents, and 3 cultural community leaders. The data collection techniques used open questionnaires and direct interviews. The results of the study show, first, that the majority of adolescents who do not know Sumang mat cause adolescent behavior became inconsistent with the values in Gayo society. Second, Sumang's form of violation is in the form of Percerakan (words), Pelangkahen (steps), Penengon (vision), and Pengunulen (sitting). Third, the factor that causes Sumang's culture to fade is due to a paradigm shift in the values of success and happiness in the Gayo community.